Silicon surface modifications produced by non-equilibrium He, Ne and Kr plasma jets. (23rd November 2016) - Engelhardt, Max; Kartaschew, Konstantin; Bibinov, Nikita; Havenith, Martina; Awakowicz, Peter
Abstract: In this publication the interaction of non-equilibrium plasma jets (N-APPJs) with silicon surfaces is studied. The N-APPJs are operated with He, Ne and Kr gas flows under atmospheric pressure conditions. Plasma bullets are produced by the He and Ne N-APPJs, while a filamentary discharge is ignited in the Kr flow. All these N-APPJs produce remarkable traces on silicon wafer surfaces treated in their effluents. Different types of etching tracks, blisters and crystals are observed on the treated surfaces. The observed traces and surface modifications of silicon wafers are analyzed with optical, atomic-force, scanning electron and Raman microscopes. Based on the material composition within the etching tracks and the position and dimension of blisters and crystals, the traces observed on the silicon wafer surfaces are interpreted as traces of micro-plasmoids. Amorphous silicon is found in the etching tracks. Blisters are produced through the formation of cracks inside the silicon crystal by the interaction with micro-plasmoids. The reason for these modifications is not clear now. The density of micro-plasmoids traces on the treated silicon surface and the depth and length of the etching tracks depends strongly on the type of the used carrier gas of the N-APPJ.